PEDAGOGY OF GENERATIVE ARTIFICIAL INTELLIGENCE IN SHAPING LITTLE COMMUNICATORS: A SYSTEMATIC LITERATURE REVIEW 2020–2025 IN THE CONTEXT OF PRESCHOOL EDUCATION IN MALAYSIA - Kadir, Rokiah; Omar, Romarzila; Abdul, Mohamad Albaree (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This systematic literature review examines the exploration of generative artificial intelligence (Generative AI) pedagogy in preschool education in Malaysia from 2020 to 2025. The study focuses on the effectiveness of generative AI-based pedagogy in shaping “little communicators,” namely preschool children who are capable of verbal, social, and creative communication. The article screening process was conducted in accordance with the PRISMA 2020 guidelines, with searches performed in MyJurnal, MyCite, Google Scholar, Scopus, and university repositories in Malaysia. The findings indicate that local research is still at an early stage, with several initiatives such as interactive chatbots, AI-based digital storytelling, and vocabulary support applications. However, teacher readiness, infrastructural challenges, and ethical and child data privacy concerns remain major constraints. Based on these findings, the implementation of generative AI in Malaysian preschool education has significant implications for policy and teaching practice. In line with the principles of the National Preschool Standard Curriculum (Kurikulum Standard Prasekolah Kebangsaan, KSPK), which emphasizes the communication pillar and holistic student development, and supporting the direction of the 2026 Preschool Curriculum (KP2026) reform that reinforces digital competence, bilingualism, and 21st-century skills, effective implementation requires alignment among curriculum documents, teacher training, digital content curation, and data safety guidelines. Generative AI has the potential to act as a catalyst in developing more confident and digitally literate “little communicators”; however, this transformation necessitates additional empirical evidence, clear policy support, and priority capacity-building programs in the implementation of KP2026.